Nicholas G. Piotrowski, Matthew’s New David at the End of Exile. A Socio-Rhetorical Study of Scriptural Quotations (Supplements to Novum Testamentum 170; Leiden – Boston: Brill 2016) - Pietrzak, Jacek (The Biblical Annals, 2017)
Book review: Nicholas G. Piotrowski, Matthew’s New David at the End of Exile. A Socio-Rhetorical Study of Scriptural Quotations (Supplements to Novum Testamentum 170; Leiden – Boston, Brill 2016). Pp. 316. €125. ISBN 978-90-04-32678-1 (hardback). ISBN 978-90-04-32688-0 (e-book).